Once bitten, twice shy? Direct and indirect effects of weather shocks on fertilizer and improved seeds use - Mulungu, Kelvin H.; Manning, Dale T.; Bozzola, Martina (Elsevier, 2025)
Evidence suggests that negative weather shocks, such as droughts, can influence input use in agriculture by reducing available income and shaping farmers' behavioral responses. Yet, the relative importance of these two pathways remains unclear. This study proposes a method to disentangle the direct (behavioral) and indirect (income) effects of a drought shock on the use of inorganic fertilizer and improved maize seed. We employed a two-way fixed-effects regression combined with causal mediation analysis and entropy balancing to account for income endogeneity on a rich farm-level data from 6058 smallholder households in Zambia in 2012 and 2015. Our results show that farmers who experienced a drought in the previous growing season are less likely to use inorganic fertilizer but more likely to use improved seeds. The indirect income effect accounts for approximately 10% of the total effect for both inputs, amplifying the direct effect for inorganic fertilizer while diminishing it for improved seeds. The contribution of the indirect effect increases with the severity of drought shocks, although the direct effect remains the dominant channel. We also provide suggestive evidence that changes in risk aversion drive behavioral responses, while access to credit mitigates the income effect. These results highlight how drought shocks influence the timing and type of technology adopted in agriculture. Understanding the relative importance of these direct and indirect effects offers critical insights for policies aimed at enhancing climate change adaptation and agricultural productivity in the developing world.